EFFECT OF RIFAMPICIN PRETREATMENT ON HIPOGLYCEMIC EFFECT OF GLYPIZIDE AMONG HEALTHY VOLUNTEERS - Luciana Kuswibawati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The incidence of tuberculosis in diabetic patients is high, therefore, the combination usage of antituberculosis (rifampicin) and antidiabetic (glypizide) medicines is inevitable. Rifampicin, an enzyme inductor, capable to influence the metabolism of other medicine when administered in concordance. The aimed of this study, therefore, was to investigate the influence of rifampicin pre-treatment on hypoglycaemic effect of glypizide (a second generation of sulphonylurea) among 12 Indonesia healthy volunteers, of both sexes. This study applied randomized crossover design receiving with and without rifampicin pre-treatment. Prior to starting the experiment, the pre-treatment group was given 450 mg of rifampicin orally daily for 7 days. Subsequently, single dose of 5 mg glypizide was administered to both of control and pre-treatment groups. The blood samples were then collected at a certain interval time for 7 hours. Glucose Oxydase (GOD) method were used to analyze the level of glucose in blood samples. The result showed no significant influence of rifampicin on hypoglycaemic effect of glypizide. However, it was found that rifampicin reduced significantly blood glucose level at 2.5 and 3 hours for 51.38 % and 20.58 %, respectively. The conclution of this study exhibit that pre-treatment with 450 mg of rifampicin daily for 7 days did not affect AUC0-7 blood glucose level as a result of single dose administration of 5 mg glypizide.Key words : rifampicin, glypizide, hypoglycaemic effect